Depolarization by Jet Precession in Early Optical Afterglows of Gamma-Ray Bursts - Bao-Quan Huang; Tong Liu; Guo-Yu Li (The Astrophysical Journal)
Polarization observations provide a unique way to probe the nature of jet magnetic fields in gamma-ray bursts (GRBs). Recently, some GRBs have been detected to be polarized in their early optical afterglows. However, the measured polarization degrees (PDs) of these GRBs are much lower than those predicted by theoretical models. In this work, we investigate the depolarization induced by jet precession in combination with the measured PDs of the GRB early optical afterglows in the reverse shock (RS) dominated phase (∼10 ^2 –10 ^3 s). We calculate the PDs of RS emissions with and without jet precession in both magnetic field configurations, i.e., aligned and toroidal magnetic fields, and meanwhile explore the effects of different parameters on the PDs. We find that the PDs are slightly affected by the configurations of the ordered magnetic fields and are positively related to the precession period. Moreover, the PDs are sensitive to the observed angle, and the measured low PDs favor a small one. Thus, as one of the plausible origins of the structured jets, jet precession could be considered as an alternative mechanism for the low PDs observed in GRB early optical afterglows.